Disruptive coloration and binocular disparity: breaking camouflage. Issue 1896 (13th February 2019) - Adams, Wendy J.; Graf, Erich W.; Anderson, Matt
Abstract : Many species employ camouflage to disguise their true shape and avoid detection or recognition. Disruptive coloration is a form of camouflage in which high-contrast patterns obscure internal features or break up an animal's outline. In particular, edge enhancement creates illusory, or 'fake' depth edges within the animal's body. Disruptive coloration often co-occurs with background matching, and together, these strategies make it difficult for an observer to visually segment an animal from its background. However, stereoscopic vision could provide a critical advantage in the arms race between perception and camouflage: the depth information provided by binocular disparities reveals the true three-dimensional layout of a scene, and might, therefore, help an observer to overcome the effects of disruptive coloration. Human observers located snake targets embedded in leafy backgrounds. We analysed performance (response time) as a function of edge enhancement, illumination conditions and the availability of binocular depth cues. We confirm that edge enhancement contributes to effective camouflage: observers were slower to find snakes whose patterning contains 'fake' depth edges. Importantly, however, this effect disappeared when binocular depth cues were available. Illumination also affected detection: under directional illumination, where both the leaves and snake produced strong cast shadows, snake targets were localized more quickly than in scenes rendered under ambient illumination. In summary, we show that illusory depth edges, created via disruptive coloration, help to conceal targets from human observers. However, cast shadows and binocular depth information improve detection by providing information about the true three-dimensional structure of a scene. Importantly, the strong interaction between disparity and edge enhancement suggests that stereoscopic vision has a critical role in breaking camouflage, enabling the observer to overcome the disruptive effects of edge enhancement.